Relationship Between Muscle Thickness and Hip and Groin Function in Elite Professional Dancers: A Cross-Sectional Correlational Study - Miguel A. Alcocer-Ojeda; Antonia Gómez-Conesa (Journal of Clinical Medicine, 2026)
Objective: The aim of the study was to sonographically evaluate the thickness of the abdominal, multifidus lumborum and gluteal muscles in professional dancers and the relationship between anthropometric, demographic and professional characteristics and clinical tests of the hip and groin. Methods: A cross-sectional study was employed, examining ultrasound imaging in 20 elite professional ballet dancers to assess the thickness of the abdominal muscles, lumbar multifidus, gluteus medius and gluteus minimus. The associations between the ultrasound variables and hip and groin function were tested using the Copenhagen Hip and Groin Outcome Score (HAGOS) and the Beighton score. The Spearman correlation coefficient was used to find the relationship between muscle thickness, Beighton score and HAGOS. Results: The increase in muscle thickness from rest to activity was greater in the transversus abdominis left (62.6%) and the internal oblique left (38.7%). The strongest correlations between muscle thickness and HAGOS were observed for the gluteus medius left at rest (0.55) and active (0.58) in Physical Function in Sport and Recreation and right active in Symptoms (0.42), Physical Function in Sport and Recreation (0.48), and Participation in Physical Activities (0.54). The correlation of the Beighton score with muscle thickness was inverse for the internal oblique left at rest (−0.50) and active (−0.48), the transversus abdominis active left (−0.52) and right (−0.56), the rectus abdominis right at rest (−0.55), and the gluteus minimus right at rest (−0.51). Conclusions: The muscle thickness of the gluteus medius was positively correlated with the HAGOS questionnaire, whereas joint hypermobility was negatively correlated with internal oblique, transversus abdominis, rectus abdominis and gluteus minimus muscle thickness. Ultrasound imaging should be considered for the measurement of muscle thickness in hip and groin pain. Trial Registration: ClinicalTrials.gov, NCT0565416. Date of registration: 8 December 2022.